CGCG clinical practice guidelines for the management of adult diffuse gliomas. Issue 2 (1st June 2016) - Jiang, Tao; Mao, Ying; Ma, Wenbin; Mao, Qing; You, Yongping; Yang, Xuejun; Jiang, Chuanlu; Kang, Chunsheng; Li, Xuejun; Chen, Ling; Qiu, Xiaoguang; Wang, Weimin; et al.
Highlights: This guideline is primarily an effort to assess the evidence for management of adult gliomas. This guideline documents the recommendations of CGCG in patients with gliomas. These recommendations are set forth for conscientious use by the practicing physician. The guideline could serve as a valuable source of information for medical professionals. Abstract: The Chinese Glioma Cooperative Group (CGCG) Guideline Panel for adult diffuse gliomas provided recommendations for diagnostic and therapeutic procedures. The Panel covered all fields of expertise in neuro-oncology, i.e. neurosurgeons, neurologists, neuropathologists, neuroradiologists, radiation and medical oncologists and clinical trial experts. The task made clearer and more transparent choices about outcomes considered most relevant through searching the references considered most relevant and evaluating their value. The scientific evidence of papers collected from the literature was evaluated and graded based on the Oxford Centre for Evidence-based Medicine Levels of Evidence and recommendations were given accordingly. The recommendations will provide a framework and assurance for the strategy of diagnostic and therapeutic measures to reduce complications from unnecessary treatment and cost. The guideline should serve as an application for all professionals involved in the management of patients with adult diffuse glioma and also as a source of knowledge for insurance companies and other institutions involved in the cost regulation of cancer care in China.